Acculturation Of Javanese Culture With Islam In Indonesia - Nasution, Asrindah; Arum, Rizky (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
The arrival of Islam was first brought by traders from Arabia their arrival was welcomed by the natives because merchants from Arabia were friendly and kind to the natives. Islam entered the archipelago through several routes, including trade, marriage, education, da'wah, etc. Java itself became one of the regions in the archipelago that became the location of the spread of Islam. Before knowing Islam, javanese people had previously embraced animism and dynamism, Hindu- Buddhism, and then converted to Islam, which was in the process The spread of Islam made the lives of the people begin to change for the better. Islam can be accepted by the javanese people, but even though they have changed their beliefs to embrace Islam, in fact various cultures and traditions from previous ancestors are still firmly held and implemented by the javanese community. The conditions that occur in Javanese society make them like living by adhering to two religions, where the teaching of the ancestors and the teaching of Islam are met and created new acculturation. The cultular mixing between Islam and the original culture of the Javanese people is called Javanese Islam. The word kejawen comes from the Javanese word which means everything related to Javanesecustoms and beliefs , in general terminology, kejawen is interpreted as a philosophy that has certain teachings , especially in building a karmic system, meaning Kejawen itself is a fusion between Islam and beliefs from traditional Javanese culture that have been inherent for hundreds of years in Javanese society like every kejawen belief also has many values and teachings of goodness that need to be practiced preservatively.